SOY PLANT AND ITS SPECIFIC MORPHO-BIOLOGICAL STRUCTURE, COMPOSITION AND ITS PLACE IN THE FOOD INDUSTRY - Bakirova Shahnoza Zokirjon qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article provides information on the origin, foreign and domestic varieties, distribution, place and economic importance of the soybean (Glycine max) plant belonging to the leguminous family, as well as its growth, development and cultivation.